Nurse-Mediated Parental Involvement in Pediatric Oncology: A Scoping Review - Dina Rasmita; Dewi Elizadiani Suza; Dwi Karina Ariadni (Jurnal Keperawatan Priority, 2026)
Parents investing time in caregiving is an essential component of their child's treatment in pediatric oncology. The literature describing the processes through which parents engage is often vague. This study collated evidence regarding engagement of parents in the care of pediatric oncology patients by nurses and care processes pertaining to nurses, and examined this evidence. A Scoping review designed according to PRISMA-ScR was conducted. The literature was collected from Scopus, Web of Science, PubMed, and CINAHL. Literature pertaining to pediatric oncology, parents, or family caregivers in the context of nursing from 2021-2026 was included. Of the 168 records, 20 studies were included. The evidence was framed as five facets of nursing: presence, information translation, family process support, coaching for home care and symptom management, and technology-supported care. Parent engagement in care was articulated through four process qualities: understanding, confidence, participation, and continuity in care from hospital to home. Evidence was most readily available for relational work and for the communication domain. Evidence was scarce for guidance on systematic discharge, preparation for home care, and inclusion of fathers and families of diverse language groups. Engagement of parents in pediatric oncology is better articulated as a process with nursing as a central element with clearly defined components rather than as a general family-centered construct.